Implementation of Marketing Communication Strategy for Alcoholic Products in Social Sensitivity and Legal Protection - Mahesa Maulana; Rachmat Kriyantono; Bambang Dwi Prasetyo (International Journal of Science and Society, 2021)
The role of marketing communication strategy is very important for companies in marketing products to their target market. Marketing communication of alcoholic beverage products which is hampered by promotion, marketing and distribution requires the right strategy in its implementation to ensure business continuity. This research has an exploratory constructivist paradigm. The purpose of this study was to determine the strategy carried out by the management of PT. Multi Bintang Indonesia as a marketing communication strategy for Bir Bintang alcoholic beverages. The research data collection method is through in-depth interviews, observation, and documentation. The data analysis of this research is descriptive qualitative. Informant data collection technique is purposive sampling at the Area Business Manager and Business Development Executive PT. Multi Bintang Indonesia Commerce. The results of the study reveal that the company's strategy is more focused on online aspects, including the use of social media, websites and e-commerce to inform products, sales, and campaigns. The form of marketing communication carried out by PT. Multi Bintang Indonesia in the form of direct and interactive marketing, sales promotion, event marketing, merchandise, personal selling, public relations, and word of mouth.